Incidence of cervical cancer after several negative smear results by age 50: prospective observational study - Rebolj, Matejka (BMJ Publishing Group Ltd., 2009)
Objective To determine the incidence of cervical cancer after several negative cervical smear tests at different ages. Design Prospective observational study of incidence of cervical cancer after the third consecutive negative result based on individual level data in a national registry of histopathology and cytopathology (PALGA). Setting Netherlands, national data. Population 218 847 women aged 45-54 and 445 382 aged 30-44 at the time of the third negative smear test. Main outcome measures 10 year cumulative incidence of interval cervical cancer. Results 105 women developed cervical cancer within 2 595 964 woman years at risk after the third negative result at age 30-44 and 42 within 1 278 532 woman years at risk after age 45-54. During follow-up, both age groups had similar levels of screening. After 10 years of follow-up, the cumulative incidence rate of cervical cancer was similar: 41/100 000 (95% confidence interval 33 to 51) in the younger group and 36/100 000 (24 to 52) in the older group (P=0.48). The cumulative incidence rate of cervical intraepithelial neoplasia grade I+ was twice as high in the younger than in the older group (P<0.001). Conclusions The risk for cervical cancer after several negative smear results by age 50 is similar to the risk at younger ages. Even after several negative smear results, age is not a good discriminative factor for early cessation of cervical cancer screening.